Assessment of Students' Progress in relationship with the type of Croatian L2 Courses - Jelaska, Zrinka (Array, 2008)
In this paper assessment of students' progress in different types of language programs is discussed, including various types of assessment of students' proficiency and achievement of specific objectives (which represent an internal perspective) such as the type and quality of students' performance within a program, teachers' satisfaction with the students' progress (i.e. course attendance and class activity). The importance of those different types of assessment will be analyzed with respect to the type of a language program: a semester (15 weeks) long course and a short (3-5 weeks) course. Both Croatian language programs at the university level in Croatia that serve as examples in this paper offer lectures on Croatian culture and both have teaching materials for Croatian language courses developed by teachers.